THE EFFECTIVENESS OF APPLYING INQUIRY BASED LEARNING MODEL IN SUPPORTING STUDENTSâ€™ CREATIVITY IN LEARNING ENGLISH - Puspitasari, Nurwinda Laili; Salam, Urai; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: This study aims to find out the effectiveness of Inquiry Based Learning (IBL) Model in supporting studentsâ€™ creativity in learning English hortatory exposition text for eleventh grade students of SMA Pontianak Academic Year 2014/2015 . This research was a quasi experimental research with non-equivalent control group design. The sample usedÂ  was purposive sampling where XI MIA 1 as the expreimental class and XI MIA 3 as the control class. Questionnaire was the tool to investigate the level of studentsâ€™ creativity in learning hortatory exposition text. The questionnaire was administered as measurement before and after the treatment. The calculation of questionnaire score was based on Likertâ€™s Scale. The calculation of effect size shows the number of 2.06 (>1.00) which is categorized as â€œstrongâ€. The data revealed that the students in experimental class got more opportunities for sharing their ideas in the IBL classroom and those opportunities resulted to the improvement of studentsâ€™ creativity. Â Keywords:Â  IBL, Creativity, Hortatory Exposition Text. Abstrak: Penelitian ini bertujuan untuk mengetahui kefektivan Inquiry Based Learning Model (IBL) dalam mendorong kreativitas siswa dalam belajar teks Bahasa Inggris hortatori eksposisi untuk siswa kelas sebelas SMA Pontianak tahun ajaran 2014/2015. Penelitian ini adalah sebuah penilitian quasi experimental dengan rancangan non-equivalent control group. Sampel yang digunakan adalah purposive sampling dimana XI MIA 1 sebagai kelas eksperimental dan XI MIA 3 sebagai kelas kontrol.Â  Questionnaire digunakan uuntuk mencari tahu tingkat kreativitas siswa dalam belajar teks hortatori eksposisi. Questionnaire digunakan sebagai tolak ukur sebelum dan sesudah perlakuan.Â  Penghitungan nilai questionnaire berdasarkan Skala Likert. Penghitungan tingkat keefetivan menunjukan hasil 2.06 (> 1.00) yang mana dikategorikan sebagai efek yang kuat. Data menyatakan bahwa siswa di kelas eksperimental mendapatkan kesempatan lebih untuk membagi ide mereka di kelas IBL dan kesempatan itulah yang meghasilkan peningkatan akan kreativitas siswa. Kata Kunci: IBL, Kreativitas, Teks Hortatori Eksposisi